PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB UNTUK MATA KULIAH HIDROLIKA PADA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN UNIVERSITAS NEGERI JAKARTA - Ahmad Roki Robbani (LPPM Universitas Negeri Jakarta, 2021)
ABSTRACT This research aims to develop web-based learning media as an alternative learning media in the Hydraulics course in the Education of Building Engineering study program, State University of Jakarta and to determine the eligibility level based on the assessment of material experts, media experts and assessment of student responses. The construction of web learning media for this hydraulics course resort to a Content Management System with the Wix platform as a cloud-based HTML website developer. This research applies the Research and Development (R&D) method with the development model used referring to Borg and Gall's research model but with the simplifications made by Emzir in the form of Research and Information Collecting, Planning, Preliminary Form of Product Development, Main Field Testing, and Final Product Revision. The data analysis that used for validating expert data is by applying the Aiken's V formula and the percentage of the Likert scale score which is interpreted into the eligibility category, while the assessment of students uses the average formula. The results of the media expert validation obtained 80% of eligibility percentage, then 76% from the material expert. Both of the expert assessments are included in the